2022
DOI: 10.3390/genes13061043
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Expansin Gene Family in the Storage Root Development of Diploid Wild Sweetpotato Ipomoea trifida

Abstract: Expansins play important roles in root growth and development, but investigation of the expansin gene family has not yet been reported in Ipomoea trifida, and little is known regarding storage root (SR) development. In this work, we identified a total of 37 expansins (ItrEXPs) in our previously reported SR-forming I. trifida cv. Y22 genome, which included 23 ItrEXPAs, 4 ItrEXPBs, 2 ItrEXLAs and 8 ItrEXLBs. The phylogenetic relationship, genome localization, subcellular localization, gene and protein structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In this study, 59 IbEXPs genes were identified from Ipomoea batatas genome, while only 37 ItfEXP genes were identified in Ipomoea trifida, suggesting that the number expansion of EXP gene family has occurred in Ipomoea batatas compared with to its diploid wild relative [55]. These 59 IbEXPs genes were divided into four subfamilies, IbEXPA, IbEXPB, IbEXLA and IbEXLB, which were similar to other plant species.…”
Section: Characterization Of Ibexps In Sweetpotatomentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, 59 IbEXPs genes were identified from Ipomoea batatas genome, while only 37 ItfEXP genes were identified in Ipomoea trifida, suggesting that the number expansion of EXP gene family has occurred in Ipomoea batatas compared with to its diploid wild relative [55]. These 59 IbEXPs genes were divided into four subfamilies, IbEXPA, IbEXPB, IbEXLA and IbEXLB, which were similar to other plant species.…”
Section: Characterization Of Ibexps In Sweetpotatomentioning
confidence: 68%
“…And it also ensures the food security in a lot of developing countries on account of its adaptation in various environmental conditions [53]. In previous study, 37 EXP genes were identified from Ipomoea trifida, which is the most possible diploid wild relative species of sweetpotato [55]. However, the Ipomoea trifida genome does not adequately represent the whole sweetpotato genome information.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative genome-wide study was performed between four Ipomoea species to evaluate valine glutamine motif-containing genes and found 40 differentially expressed genes (DEGs) referring to various abiotic stresses [ 26 ]. The other genome-wide studies in different Ipomoea species were conducted for important TF families such as NAC ( NAM , ATAF , and CUC ) TFs family [ 27 ], hydroxycinnamate-CoA quinate hydroxycinnamoyl transferase gene family [ 28 ], DNA-binding with one finger (Dof) TF family [ 29 ], myeloblastosis (MYB) gene family [ 30 ], phytochrome-interacting factors [ 25 ], domain of unknown function gene family [ 31 ], two-component system genes [ 32 ], xyloglucan endotransglucosylase/hydrolase gene family [ 33 ], expansin gene family [ 34 ], glycine-rich RNA-binding proteins [ 35 ], WRKY TFs family [ 36 ], zinc-finger domain-containing stress-associated proteins [ 37 ], plant-specific GRAS TFs [ 38 ], APETALA2/ethylene responsive factor (AP2/ERF) TFs family [ 38 ], jasmonate-ZIM (JAZ) TF family [ 39 ], and bZIP TF family [ 10 ]. These studies provide new insights for understanding the different TFs families-mediated stress responses and lays the foundation for future functional investigation of sweet potato TFs families.…”
Section: Genome-wide Survey Of Tf Families and Their Response To Vari...mentioning
confidence: 99%
“…Expansin family genes have been found to contain two domains (DPBB_1 and Pollen_allerg_1), and show four subfamilies: EXPA (α-expansin), EXPB (β-expansin), EXLA (expansin-like A), and EXLB (expansin-like B) [ 19 , 20 , 21 ]. The differential number of expansin genes contained in many plants, such as 34 in Arabidopsis thaliana , 38 in rice ( Oryza sativa ), 37 in sweet potato ( Ipomoea batatas ), 82 in moso Bamboo ( Phyllostachys edulis ), 56, 58, and 60 in Brassica rapa , Brassica oleracea and Brassica nigra , 30 in jujube ( Ziziphus jujuba ), 36 in potato ( Solanum tuberosum ), 75 in wild soybean ( Glycine soja ), and so on [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In bread wheat ( Triticum aestivum ), the genes number of expansin family has been found for several articles to be 87, 128, 241, and 104 [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%